The Influence of Interpersonal Communication and Work Environment on Teacher’s Performance - Adriana Lolita; Fitria, Happy; Rohana, Rohana (Yayasan Sembilan Pemuda Indonesia, 2024)
This study aims to find out, whether or not there is an influence of interpersonal communication and the work environment on teacher performance in Public High Schools in East Prabumulih District, Prabumulih City. This research was carried out using a sampling technique using saturated sampling, namely the technique of determining the sample when all members of the population are used as samples. This is done by 110 teachers, so the research data samples will be conducted on all population numbers so that the research is carried out to obtain the maximum level of accuracy so that this research will be more reliable. The results of the study show that there is a significant effect of interpersonal communication on teacher performance, work environment on teacher performance, and the simultaneous influence of interpersonal communication and work environment on teacher performance in public high schools in East Prabumulih District, Prabumulih City.